Complete mitogenome, phylogenetic and SNP-data analysis of jakumaru (Bos taurus), a prime bull from a Peruvian breeding core herd - Estrada Cañari, Richard (2025)
This study provides a comprehensive mitochondrial genome sequence and a phylogenetic analysis of Jakumaru (Bos taurus), a prominent bull from a Peruvian breeding program. The mitochondrial genome, spanning 16,340bp, comprises 13 protein-coding genes, 22 tRNA genes, and 2 rRNA genes, with a GC content of 40%. The gene arrangement and structural organization are highly conserved, closely resembling those of related Bovine species, indicating a stable genomic architecture essential for mitochondrial function. Phylogenetic analysis, incorporating 35 complete bovine mitochondrial genomes, positions Jakumaru within Subclade I, revealing a close relationship with European Simmental cattle. The study emphasizes the biological diversity and the evolution of the Simmental breed, influenced by natural selection, breeding practices, and genetic drift. These findings enhance our understanding of the breed's genetic variation and its evolution, particularly in the context of its importance in Peru